Dietary Intake and Nutritional Status of Javanese Women in Rice Producing Areas: a Comparison between Lactating and Non-lactating Women - Ilmia Fahmi; Ratna C Purwestri; Judith Lauvai; Ziba Barati; Whelma Bell; Nia Novita Wirawan (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2021)
Maintaining optimal maternal nutrition is essential for the mother’s health and the child’s growth and development. Throughout the lactating period, maternal nutrition is significant due to the child’s high nutritional needs. Therefore, an increase in food consumption is necessary. This research aimed to analyze the dietary intake and nutritional status of lactating and non-lactating women living in rice-producing areas in Central Java, Indonesia. A cross-sectional study was conducted from December 2014 to February 2015 in Demak Regency. As many as 375 participants were recruited and analyzed in this study. The results showed that the mean BMI-score of non-lactating mothers was higher than that of breastfeeding mothers (p=0.039). However, the nutritional status between the two groups of women was not significantly different. Significantly more lactating women consumed dark green leafy-colored vegetables (68.8%) and other vegetables (59.2%) than the non-lactating mothers (54.4%, p=0.065 and 36.8%, p=0.001, respectively). Regarding the selected macro and micronutrient intakes, statistically significant differences between the two groups of women could not be proven. In short, dietary intake between women within the different physiological statuses and BMI categories showed that they consumed around the same amount of macro-and micronutrient intakes and food groups, except for the high vegetable consumption among lactating women.